Bifunctional Electrocatalysts for Overall Water Splitting from an Iron/Nickel‐Based Bimetallic Metal–Organic Framework/Dicyandiamide Composite. (20th June 2018) - Zhao, Xiaojia; Pachfule, Pradip; Li, Shuang; Simke, Jan Ron Justin; Schmidt, Johannes; Thomas, Arne
Abstract: Pyrolysis of a bimetallic metal–organic framework (MIL‐88‐Fe/Ni)‐dicyandiamide composite yield a Fe and Ni containing carbonaceous material, which is an efficient bifunctional electrocatalyst for overall water splitting. FeNi3 and NiFe2 O4 are found as metallic and metal oxide compounds closely embedded in an N‐doped carbon–carbon nanotube matrix. This hybrid catalyst (Fe‐Ni@NC‐CNTs) significantly promotes the charge transfer efficiency and restrains the corrosion of the metallic catalysts, which is shown in a high OER and HER activity with an overpotential of 274 and 202 mV, respectively at 10 mA cm −2 in alkaline solution. When this bifunctional catalyst was further used for H2 and O2 production in an electrochemical water‐splitting unit, it can operate in ambient conditions with a competitive gas production rate of 1.15 and 0.57 μL s −1 for hydrogen and oxygen, respectively, showing its potential for practical applications.